The regulatory network behind MHC class I expression. (September 2019) - Jongsma, Marlieke L.M.; Guarda, Greta; Spaapen, Robbert M.
Highlights: The NLR family member NLRC5 is a regulator of MHC class I transcription. The knowledge on the mechanisms behind basal MHC class I transcription is very limited. Genome-wide and other high-end screening approaches will uncover the unknowns of MHC class I transcription in the near future. Abstract: The MHC class I pathway, presenting endogenously derived peptides to T lymphocytes, is hijacked in many pathological conditions. This affects MHC class I levels and peptide presentation at the cell surface leading to immune escape of cancer cells or microbes. It is therefore important to identify the molecular mechanisms behind MHC class I expression, processing and antigen presentation. The identification of NLRC5 as regulator of MHC class I transcription was a huge step forward in understanding the transcriptional mechanism involved. Nevertheless, many questions concerning MHC class I transcription are yet unsolved. Here we illuminate current knowledge on MHC class I and NLRC5 transcription, we highlight some remaining questions and discuss the use of quickly developing high-content screening tools to reveal unknowns in MHC class I transcription in the near future.